Peran Madarasah Diniyah Dalam Mengembangkan Pendidikan Untuk Menghadapi Era Revolusi Indrustri 4.0 - Kurvaliany, Sukma Ayu; Romadhon, Yanuar Fajar; Sya’adah, Zahrotus; Melina, Zulfa Ihza (Al-Riwayah : Jurnal Kependidikan, 2020)
Madrasah diniyah and pondok pesantren are educational institutions that are very popular in Indonesia. Todays, the role of madrasah diniyah in supporting Islamic learning needs serious attention. The development of Islamic education institutions left behind with the development of science and technology in the era of the industrial revolution 4.0. The existence of Madrasah Diniyah was fade and left behind in various aspect. This paper aims to know the problems of madrasah diniyah in the era of the industrial revolution 4.0. The method we use is literature review. This study recommends that madrasah diniyah should play a central role in the globalization era, especially in industrial revolution 4.0 era. In addition, pesantren do not only focus on studying religion and reciting the Koran, but also instill the values ​​of nationalism as well as moral and manners, and instill skills education so that madrasah diniyah can interact with the development of science and technology.